Cloud Manufacturing - WANG, SIQING (2019)
Cloud manufacturing, which developed from cloud computing by sharing information and using it for manufacturing purpose, is one of the much-anticipated technique for different companies to implement in practice and to achieve the leagilty of supply chain to meet the changing customized demand in time at the minimum cost today. This paper focuses on the exploration of the real form of Cloud Manufacturing that can be used in practice by matching its conceptions with the existing operational processes of Additive Manufacturing and how it affects the characteristics of supply chain of a company. The research method used in this paper is composed of a literature review on the concept of cloud computing, cloud manufacturing, supply chain of Additive Manufacturing, and the characteristics of supply chain. Followed by an identification of current state of Additive Manufacturing Industry and the analysis of four 3D-Printing Websites, which are divided into two types of Additive Manufacturing: End- customer Additive Manufacturing and 3D printer-owner Additive Manufacturing, by using the conception of Cloud Manufacturing System to match the operational processes of these websites with that conception and thus to verify the existence of the real form of Cloud Manufacturing. The findings from this research provide evidence about there are some limitations of Additive Manufacturing and they caused the gap between Additive Manufacturing and Cloud Manufacturing, which restrict the existing operational process of 3D-printing websites to become the practical form of Cloud Manufacturing. The main conclusion of this study is that the real form of cloud manufacturing exists in when different additive manufacturing combines with relevant cloud manufacturing platform scenario, which is developed in the discussion, and the combination of them have some significant impact on the supply chain of different additive manufacturing. This dissertation recommends some further studies on developing more technology and software support for the advance of cloud manufacturing and exploring the way to improve the public awareness and social acceptance about cloud manufacturing so that it can have its customer support in the marketplace.